Twelve tips for medical students experiencing an interruption in their academic progress. (3rd October 2022) - Carr, Sandra E.; Canny, Ben J.; Wearn, Andy; Carmody, Dianne; Celenza, Antonio; Diug, Basia; Leech, Michelle; Wilkinson, Tim J.
Abstract: For every commencing cohort of medical students, a small but significant number will experience an interruption to their academic progression because of academic difficulties, health concerns or external influences outside of the students' control. During the process of researching the factors surrounding difficulties with academic progression, students told us many ways that they have learned from that experience, which then allowed most of them to graduate. This paper combines the shared experiences of students who have had an interruption, and those of the authors as medical educators.